Hot Deformation Behavior of C-Mn Steel with Incomplete Recrystallization during Roughing Phase with and without Nb Addition - Grega Klančnik; Jan Foder; Boštjan Bradaškja; Mina Kralj; Urška Klančnik; Paul Lalley; Douglas Stalheim (Metals, 2022)
The objective of the study is to improve understanding of the practical role of niobium (Nb) in the case of industrial inconsistent rolling processes such as the rolling of heavy gauge plates where a lower stored energy rolling practice will result in a less stable and less repeatable static recrystallization (SRX) activation that prevents complete recrystallization. In the current study, these variabilities are validated by comparing the mean flow stress (MFS) indirectly determined from the rolling force measured on a reverse four-high rolling mill stand. The material resistance to deformation and grain size evolution of a C-Mn steel during hot rolling was observed and validated with and without Nb addition. The pre-defined rolling schedule was predicted to exhibit incomplete recrystallization in the roughing phase due to the limited stored energy of deformation that resulted from low rolling loads and a higher number of rolling passes. The prior austenite grain size (PAGS) distribution was predicted and compared to the measured effective ferrite grain (FG) size distribution after the completion of hot rolling and phase transformation achieved using natural air plate cooling. Both the predicted PAG and measured FG distributions revealed the presence of multimodality, and both distributions were used for grain size reduction factor determination for γ → α transformation for the current study with 1.96 for 0 Nb and 1.70 for 240 Nb. The results presented in this paper are not only limited to the rolling schedule used in this paper because instabilities resulting in incomplete austenite conditioning are also observed when evaluating the cross-sections of other heavy plates and various steel grades utilizing different processing routes with comparable compositions such as modern lean abrasion-resistant steels, regular line pipe steels, and other similar grades.